LEGAL PROTECTION FOR CHILDREN - Sri Utami; Hepy Krisman Laia; Muhammad Arif Sahlepi (PT. Sinergi Legal Publisher, 2025)
The purpose of this study is to determine the forms of violence against children and the legal protection provided to children as victims of crime under Indonesian criminal law. Legal protection for children is a crucial issue that requires serious attention from various parties, including the government, society, and families. Children have fundamental rights that must be protected to ensure their proper growth and development. This paper discusses the concept of legal protection for children, the legal basis underlying child protection in Indonesia, as well as the challenges and solutions that can be implemented to improve legal protection for children.